A Study on SDN for an Optimized Network and Power in Traffic Engineering - Gunasekar, K.; Vanitha, P.; Kavitha, K.; Navamani, C. (International Journal of Psychosocial Rehabilitation, 2024)
A crucial technique to optimize a network and improve network strength is traffic engineering. As traffic demand will increase, traffic engineering will cut back service degradation and failure within the network. To allow a network to adapt to changes within the path, the research community proposed several traffic engineering techniques for the traditional networking architecture. However, the standard specification is troublesome to manage. Software Defined Networking (SDN) is a new networking model, which decouples the control plane and data plane of the networking devices. It guarantees to change network management, introduces network programmability, and provides a global view of network state. To exploit the potential of SDN, new traffic engineering ways are needed. This paper surveys traffic engineering for SDN. It focuses on some of the traffic engineering methods for SDN-based networks. This paper conjointly explores the reviews and future directions for SDN traffic engineering solutions.